Tawasul dalam Tradisi Islam: Analisis Komprehensif Tafsir, Hadis, dan Praktiknya di Indonesia - Afif Kholidin; Muhammad Syahrul Mubarak; Nabila Umayrah; Saifudin Zuhri; Natasya Fakhira Sukma (IAIN KENDARI, 2026)
This study examines the discourse of tawassul in Islam by focusing on the relationship between religious textual normativity and the socio-religious practices of Indonesian Muslims. The study aims to analyze the epistemological differences between puritan and traditionalist groups in understanding the concept of wasilah, while also proposing a moderate construction through reinterpretation of tawassul. This research employs a qualitative library-based approach using contextual hermeneutics, sociology of knowledge, and critical discourse analysis. The findings reveal that the debate on tawassul is not merely related to ritual law, but also concerns spiritual authority, religious identity, and the relationship between texts and local traditions. Puritan groups restrict tawassul to righteous deeds and prayers from living pious people, while traditionalists interpret it as a spiritual medium ultimately directed to Allah. This study proposes a reinterpretation of wasilah based on maḥabbah as a model of religious moderation capable of bridging theological integrity and Indonesian Muslim religious traditions.